Personal values of university students in Mexico and in Oregon - Simmons, Dale D. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Simmons Value Survey, a 100 statement inventory developed through a survey of available systems for assessing personal values, was administered to students in the Preparatoria and Filosofía y Letras programs at the Universidad de Guadalajara as well as to students taking General Psychology at Oregon State University. Findings were: ( 1 ) the overall value priority systems of the groups were significantly correlated, even though there were many significant differences between groups in the valuing of specific statements; (2) there was no significant difference between groups in overall level of valuing; (3) correlation between male and female norms within national groups approximate reliability coefficients (i.e., .91 and .95), reducing any need to establish separate norms for each sex; (4) little support was gained for the active-passive syndrome distinction between Mexican and United States orientations, at least as far as the university students are concerned. Specific values characterizing and distinguishing the student groups are presented.